ENVIRONMENTAL IMPACT ASSESSMENT USING LIFE-CYCLE ANALYSIS - Olutayo Opeyemi Ogunmilua; Isaque Moyses Guimaraes; Efe Peter Iyomi; Edidiong Uboho (International Journal of Innovations in Engineering Research and Technology, 2021)
Life cycle assessment (LCA) is a methodology used in evaluating the impact of environmental factors associated with all stages of a commercial product, process, or service life cycle. This paper sheds light on different techniques and processes and how they are applied during each phase of a product or process, right from the acquisition of raw materials to the end-of-life phase where assets are decommissioned. This project also uses a case study to explore economic and ecological life cycle outcomes as it relates to cost and financial bearing